The effects of drainage on the rates of early wound complications and recurrences after Limberg flap reconstruction in patients with pilonidal disease - Kirkil, C.; Boyuk, A.; Bulbuller, N.; Aygen, E.; Karabulut, K.; Coskun, S. (Springer, 2011)
Background Cavity drainage has been used routinely in Limberg flap repair for pilonidal disease but there have been few controlled studies on the rationale for routine usage of drains. The aim of this study was to determine whether routine cavity drainage affects the rates of early wound complications and recurrences after rhomboid excision with Limberg flap repair for pilonidal disease. Methods Sixty patients with pilonidal disease in the sacrococcygeal region were randomized sequentially into 2 groups as drained or non-drained. All of them underwent rhomboid excision and Limberg flap reconstruction. The patients were followed up by physical examination at 2 and 4 weeks after the operation and every 6 months thereafter. Results Two patients in the drained group and 3 patients in the non-drained group were excluded from the study because of non-attendance at the follow-up physical examinations. The average length of hospital stay was 3.1 +/- A 0.9 and 3.3 +/- A 0.8 days in the drained and non-drained groups, respectively. There were 5 seromas, 2 wound dehiscences and 1 hematoma in the non-drained group, while 3 seromas and 2 wound dehiscences developed in the drained group. The complication rates of groups were similar (29.6% in the non-drained group vs. 17.8% in the drained group). Pilonidal disease recurred in 2 patients in the drained group who had wound dehiscence and in 3 patients in the non-drained group who had wound dehiscence or seroma. Conclusions Routine usage of drains for Limberg flap reconstruction in the sacrococcygeal region did not affect wound-related complications and recurrence rates.
Keywords: Drain; Limberg flap; Pilonidal disease; Recurrence